Innovation and export in SMEs: the role of relationship banking - Frazzoni, Serena (2022)
This paper assesses the role of relationship lending in explaining simultaneously the innovation activity of Small and Medium Enterprises (SME), their probability to export (i.e. the extensive margin) and their share of exports on total sales conditional on exporting (i.e. the intensive margin). We adopt a measure of informational tightness based on the ratio of firm’s debt with its main bank to firm’s total assets. Our results show that the strength of the bank-firm relation has a positive impact on both SME’s probability to export and their export margins. This positive effect is only marginally mediated by the SME’s increased propensity to introduce product innovation. We further discuss the financial and non-financial channels through which the intensity of bank-firm relationship supports SMEs’ international activities.